Perbandingan Produksi dan Kadar Gula Salak Sidimpuan (Salacca sumatrana Becc) Di Dataran Rendah Dan Dataran Tinggi - Rasmita Adelina; Yusriani Nasution; Jamaluddin Jamaluddin (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2018)
The center of planting salak Sidimpuan in the district of West Angkola is in highlands, whereas the center of planting Sidimpuan Snake Fruit in South Angkola in the district is in lowland. Fruits of Sidimpuan Snake Fruit are originated from West Angkola, generally tastes sweeter compared with salak of South Angkola. Differences of altitude level from salak planting area is suspected to be one of the factors causing the different levels of sweetness and production salak Sidimpuan. This research was conducted in district of West Angkola and district of South Angkola with altitude of 600-700 m asl and 200-300 m asl, starting from December until January 2017. Analysis of salak sugar level was done at Agricultural Faculty Laboratory of Graha Nusantara University, Padang Sidimpuan. The method was used in this research is survey and purposive sampling. To determine the comparison of production and sugar content of Sidimpuan Snake Fruit in lowland and high plains were analyzed using an independent t-test. The results showed that the comparison of Sidimpuan Snake Fruit production in the plateau (1,231 kg per tree) was significantly different with the production of Salak Sidimpuan in the lowlands (0.991 kg per tree). The comparison of sugar content of Sidimpuan Snake Fruit in highland area (10,550%) was significantly different with sugar content of Sidimpuan Snake Fruit in lowland area (9,100%).